Pythagoras Tree Applied For Determined Instagram Usage Habit Decision - Ambarsari, Erlin Windia; Herlinda, Herlinda (Sinkron : Jurnal dan Penelitian Teknik Informatika, 2020)
In previous studies, Pythagoras Tree constructed using the Regression Method, namely ID3 of Standard Deviation Reduction (SDR). The study using SDR for Classification. Data obtained from previous research about Instagram Usage. The result of the study that SDR is useful for the classification method for constructing Pythagoras Tree. However, the target attribute is must use a numerical variable to gain the Standard Deviation and the Mean. Empty data does not affect calculations. Although instances must be discarded, thereby reducing the amount of data. For the case of the Instagram Usage Habit itself, not getting the right pattern to deciding due to the data obtained is less. However, Construct Pythagoras Tree successfully done.